2010
DOI: 10.3109/00365521.2010.497936
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and long-term prognosis of Crohn's disease in Korea

Abstract: Korean CD patients differed from Western patients in gender distribution, disease location, and perianal fistula occurrence. Korean CD patients may also have better clinical courses than Western patients, as indicated by the lower intestinal resection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
123
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(159 citation statements)
references
References 39 publications
28
123
7
1
Order By: Relevance
“…Congruent with previous Asian studies, including data from China (14,16,24,46) , Japan (2,15,27,43) , Korea (42,44) , Singapore (21) , India (9) and Sri Lanka (35) , our observation have demonstrated a male predominance in CD, which is discordant with majority of the western studies. Such discrepancy may be sex-related differences in triggering or predisposing factors of CD between Asian and Western populations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Congruent with previous Asian studies, including data from China (14,16,24,46) , Japan (2,15,27,43) , Korea (42,44) , Singapore (21) , India (9) and Sri Lanka (35) , our observation have demonstrated a male predominance in CD, which is discordant with majority of the western studies. Such discrepancy may be sex-related differences in triggering or predisposing factors of CD between Asian and Western populations.…”
Section: Discussionsupporting
confidence: 73%
“…The use of IS therapy in Asia varies between countries. A Korean single-centre study reported that thiopurines were used in only 63% of CD patients (44) . This phenomenon may relate to limited experience in managing CD and use of IS medications.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] All patients with CD or UC were diagnosed at the IBD Clinic of Asan Medical Center, Seoul, Korea on the basis of clinical, radiologic, endoscopic and histopathologic criteria. [37][38][39] Patients with indeterminate colitis were excluded from the study. Disease-free individuals recruited from the Health Promotion Center of the Asan Medical Center (based on routine health checkups) were employed as controls.…”
Section: Study Populationmentioning
confidence: 99%
“…For example, the NOD2 or ATG16L1 variants, which are regarded as firmly established CD susceptibility genes among whites, are not associated with CD in Asian populations, [1][2][3][4][5] whereas the association of the TNFSF15 variants with a CD risk is stronger in Koreans and Japanese than in whites. [6][7][8] Korean CD patients also differ from western patients in that they have a male predominance in sex distribution, 9,10 predominance of ileocolonic disease in the disease location, [9][10][11] and a higher incidence of perianal fistula in disease behavior. 10,11 Therefore, it is possible that the clinical course of CD differs between Asian and western patients.…”
mentioning
confidence: 95%
“…[6][7][8] Korean CD patients also differ from western patients in that they have a male predominance in sex distribution, 9,10 predominance of ileocolonic disease in the disease location, [9][10][11] and a higher incidence of perianal fistula in disease behavior. 10,11 Therefore, it is possible that the clinical course of CD differs between Asian and western patients.…”
mentioning
confidence: 95%